(untitled) (CIPEEX, 2022)
&NBSP; TRAINING AN EGRESS WITH MOTOR, COGNITIVE AND AFFECTIVE SKILLS IS AMONG THE GENERAL OBJECTIVES OF THE DENTISTRY COURSE OF THE UNIVERSITY CENTER OF ANÁPOLIS. THE DISCIPLINE OF MORPHOLOGY AND DENTAL SCULPTURE HAS THE MISSION TO INITIATE THIS DEVELOPMENT USING ACTIVE METHODOLOGIES OF TEACHING AND LEARNING, EXPERIMENTATION, SEARCH FOR KNOWLEDGE, CURIOSITY AND AWARENESS OF THE ART OF BEING A DENTIST. THE OBJECTIVE OF THIS WORK IS TO PRESENT SOAP SCULPTURES PERFORMED BY ACADEMICS OF THE 1ST PERIOD OF THE DENTISTRY COURSE OF THE UNIVERSITY CENTER OF ANÁPOLIS - UNIEVANGLICA.PARA THE ACADEMICS WERE INSTRUCTED, ON THE FIRST DAY OF CLASS, TO MAKE A SCULPTURE FREE OF SOAP, INSPIRED BY ANY ELEMENT, USING THE LECRON INSTRUMENTS. THIS SCULPTURE SHOULD BE CREATIVE, ORIGINAL, INDIVIDUAL AND WITHOUT HELP OR EXTERNAL INTERVENTION. THE DEADLINE WAS 7 DAYS. 75 SCULPTURES WERE HANDED OUT, AMONG THESE 29 TEETH AND 46 OF DIVERSE ELEMENTS. THE MATERIAL WAS PREVIOUSLY SELECTED BY THE TEACHERS OF THE DISCIPLINE AND THEN BY A TEACHER’S GROUP, THE 20 BEST SCULPTURES WERE CHOSEN. DURING THE 7 DAYS OF THE WORK, THE SPATIAL, INTRAPERSONAL, AND BODY-KINESTHETIC INTELLIGENCES WERE EXPLORED THROUGH PLANNING FOR THE WORK, SEARCH FOR TECHNIQUES AND KNOWLEDGE FOR SCULPTURE, SELF-CONTROL, MASTERY OF MOVEMENTS AND ABSTRACTION CAPACITY. IN THIS WAY THE ACADEMICS WERE ABLE TO EXPLORE NEW SKILLS AND SENSATIONS, IMPROVE THEIR PERCEPTION AND IMMERSE THEMSELVES IN THE RECENTLY PRESENTED UNIVERSE OF DENTISTRY. IT IS CONCLUDED THAT THE NEW ENTRANTS OF THE COURSE FELT MOTIVATED AND INSTIGATED TO PRODUCE AND LEARN MORE. KEYWORDS: DENTAL MORPHOLOGY. SCULPTURES. MULTIPLES INTELIGENCES. &NBSP;